Rheumatic heart disease among adults in a mining community of Papua, Indonesia: findings from an occupational cohort. Issue 2 (28th July 2015) - Rodriguez-Fernandez, Rodrigo; Amiya, Rachel; Wyber, Rosemary; Widdodow, Wishnu; Carapetis, Johnathan
Abstract : Background: Rheumatic heart disease (RHD) remains a significant cause of cardiovascular morbidity and mortality in developing countries such as Indonesia. Yet, despite being one of the most readily preventable chronic diseases, RHD has received scant research or policy attention, particularly in South-East Asia. Aim: To describe the pattern of RHD occurrence in a sample of presenting cases from an occupational cohort in Papua Province, Indonesia. Methods: Clinical records of 15 608 mining workers (96.4% men, mean age 36.3±7.4 years) were reviewed retrospectively to identify and extract data on all rheumatic fever (RF) and RHD cases admitted to two hospitals in Papua during 2008–2013. Collected data included basic demographics, employment history and echocardiographic findings. Results: 83 RHD cases (95.6% men, mean age 39.6±12.5 years) and 3 RF cases were identified between 2008 and 2013. Increased RHD risk was observed among those aged 35–44 (HR=3.60) and 45–68 (HR=4.46) years relative to the youngest age group (p<0.01). RHD incidence density was 6.84 per 10 000 person years of follow-up. Among cases, mitral stenosis was the most common valvular lesion at initial presentation (41.0%), and 6.0% were multivalvular. Conclusions: The prevalence of RHD in Papuan mining workers correlates with adult prevalence data in other populations with a high RHD burden, highlighting RHD as a significant health issue into adulthood. The late stage at which most patients presented points to a strong need for earlier intervention. Both primary and secondary preventive measures must be considered critical tools to prevent and reduce RHD burden, particularly among older age groups.